2015
DOI: 10.1038/srep18111
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Chinese herbal medicine for cancer palliative care: overview of systematic reviews with meta-analyses

Abstract: Chinese herbal medicines (CHM) are often used in managing cancer related symptoms but their effectiveness and safety is controversial. We conducted this overview of meta-analyses to summarize evidence on CHM for cancer palliative care. We included systematic reviews (SRs) with meta-analyses of CHM clinical trials on patients diagnosed with any type of cancer. Methodological quality of included meta-analyses was assessed with the Methodological Quality of Systematic Reviews (AMSTAR) Instrument. Fifty-one SRs wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 29 publications
(34 reference statements)
0
31
0
1
Order By: Relevance
“…They were selected as they had critically appraised and summarized the most up-to-date clinical evidence on CHM, as well as acupuncture and related therapies, for cancer palliative care at the time of our study. In these rigorous syntheses, 2 - 6 methodological quality of 74 included SRs was evaluated using the AMSTAR instrument, 28 while risk of bias of 88 included randomized controlled trials (RCTs) were assessed with the Cochrane risk of bias tool. 29 Strengths and limitations on the synthesized evidence were also highlighted by the original authors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They were selected as they had critically appraised and summarized the most up-to-date clinical evidence on CHM, as well as acupuncture and related therapies, for cancer palliative care at the time of our study. In these rigorous syntheses, 2 - 6 methodological quality of 74 included SRs was evaluated using the AMSTAR instrument, 28 while risk of bias of 88 included randomized controlled trials (RCTs) were assessed with the Cochrane risk of bias tool. 29 Strengths and limitations on the synthesized evidence were also highlighted by the original authors.…”
Section: Methodsmentioning
confidence: 99%
“…29 Strengths and limitations on the synthesized evidence were also highlighted by the original authors. [2][3][4][5][6] By identifying statistically significant favorable results from these synthesis, [2][3][4][5][6] our study focused on a total of 7 CM interventions. Results of these interventions were displayed in 7 evidence profiles, which presented in a consistent format: number of studies; number of participants; effects of binary and continuous outcomes including their corresponding 95% confidence intervals (CIs) and P values; and quality of evidence.…”
Section: Part 1: Preparation Of Evidence Profiles and Etd Framework mentioning
confidence: 99%
“…Beyond ATO, the general study of TCM-derived natural products and compound formulations for cancer therapy is an area of immense interest both within and outside China. Apart from the ongoing discovery and characterisation of active antineoplastics, the use of TCM as an effective adjuvant therapy in combination with conventional treatments as well as the role of TCM in pain management and palliative care should also not be overlooked (Refs 102, 103, 104, 105, 106, 107). For instance, the four-herb formulation PHY906 currently undergoing multiple clinical trials has been identified as an effective modulator of chemotherapy toxicity for multiple chemotherapy treatments (Refs 108, 109, 110).…”
Section: Arsenic Trioxide In the Treatment Of Acute Promyelocytic Leumentioning
confidence: 99%
“…Chinese herbal medicine (CHM) has been used for centuries for the treatment of various ailments in China and is believed to be beneficial to patients [7]. Many studies have examined the individual components responsible for the anticancer activities of various herbs, and these components have been shown to dramatically affect the survival of cancer cells and/or to enhance the patient's immunity when used as the sole cancer therapy [8].…”
Section: Introductionmentioning
confidence: 99%